Computer simulation of diabetic retinopathy screening adherence: Agent based model with fuzzy logic - Pereira, A.; Laureano, Raul M. S.; Neto, F.; Macedo, J. (2021 16th Iberian Conference on Information Systems and Technologies (CISTI), 2021)
Abstract: Diabetic retinopathy is a major cause of blindness in developed countries. Since this disease remains asymptomatic in the early stages, periodic screening is of utmost importance. However, the success of screening programmes depends largely on the adherence of the target population. Thus, the development of computer simulations that make it possible to understand the factors correlated with the individual decision to adhere to the screening or not, to predict low adherence rates and to define strategies that promote its increase, is very useful. The aim of the present research is to demonstrate that it is possible to simulate the behavior of adherence to screening, using a model with a high degree of abstraction and scalability. To this end, a model based on agents with fuzzy logic was developed, calibrated, and validated using real data from 271,867 calls for screening in the Northern Regional Health Administration. The results obtained are very close to the real ones, both in the training and in the test sets, which attests to the validity of the model for the study of this problem and use as a predictive tool for public health planning. Resumo: A retinopatia diabética é uma das principais causas de cegueira nos países desenvolvidos. Uma vez que esta doença permanece assintomática nos estádios iniciais, é da máxima importância a realização de rastreios periódicos. No entanto, o sucesso dos programas de rastreio depende em grande parte da adesão da população alvo. Assim, o desenvolvimento de simulações computacionais que permitam compreender os fatores correlacionados com a decisão individual de aderir ou não ao rastreio, prever baixas taxas de adesão e definir estratégias que promovam o seu aumento, reveste-se de grande utilidade. O objetivo da presente investigação é demonstrar que é possível simular o comportamento de adesão ao rastreio, através de um modelo com elevado grau de abstração e escalabilidade. Para tal, foi desenvolvido um modelo baseado em agentes dotados de lógica fuzzy, calibrado e validado com recurso a dados reais de 271.867 convocatórias para rastreio na Administração Regional de Saúde do Norte. Os resultados obtidos são muito próximos dos reais, quer no grupo de treino, quer no grupo de teste, o que atesta a validade do modelo para o estudo desta problemática e uso como ferramenta preditiva para planeamento em saúde pública.